Toward tripartite hybrid entanglement in quantum dot molecules - M Khoshnegar; A Jafari-Salim; M H Ansari; A H Majedi (New Journal of Physics, 2014)
Establishing the hybrid entanglement among a growing amount of matter and photonic quantum bits is necessary for scalable quantum computation and long-distance quantum communication. Here we demonstrate that charged excitonic complexes forming in strongly correlated quantum dot molecules are able to generate tripartite hybrid entanglement under proper carrier quantization. The mixed orbitals of the molecule construct multi-level ground states with sub-meV hole tunneling energy and relatively large electron hybridization energy. We show that appropriate size and interdot spacing keeps the electron particle weakly localized, opening extra recombination channels by correlating ground-state excitons. This allows for creation of higher order entangled states. Nontrivial hole tunneling energy, renormalized by multi-particle interactions, facilitates the realization of the energy coincidence among only certain components of the molecule optical spectrum. This translates to the emergence of favorable spectral components in a multi-body excitonic complex which sustain principal oscillator strengths throughout the electric field-induced hole tunneling process. We particularly analyze whether the level broadening of favorable spin configurations could be manipulated to eliminate the distinguishability of photons.